A simulation-based method for inventory ownership planning of aircraft spare engines and parts. (2016) - Ramirez-Hernandez, Jose; Oakley, Steven; Zhang, Mei; Scalise, Alejandro
The planning of spare engines and engine parts is a challenging and critical task for airlines to seamlessly support flying and engine repair operations. Engines are expensive and critical assets that make this problem important from the financial and operational perspectives. Thus, this paper presents a simulation-based method for planning the required spare ownership levels for engine spares and engine parts. The models presented are utilised in single and multi-location settings and can be used to provide estimations of the minimum spare ownership required to meet given service levels and performance metrics based on out-of-service aircraft events. Two levels of modelling are provided: a higher level where the repairable items are the engines as a whole, and a lower level that focuses on the repair of the individual engine components. Two simulation studies with actual industry data are also presented to illustrate the application of our models.